2010
DOI: 10.1021/es9038243
|View full text |Cite
|
Sign up to set email alerts
|

Organic Micropollutant Degradation in Sewage Sludge during Composting under Thermophilic Conditions

Abstract: Degradation of 12 common organic micropollutants in sewage sludge representing bactericides, flame retardants, fragrances, vulcanizers, and plasticizers (part of many common products) during thermophilic composting was investigated. Micropollutant concentrations, compost temperature, water content, and organic matter content were measured over 24 days in a full-scale compost windrow made from digested sewage sludge, yard waste, and horse manure. Composting took place indoors, and the windrow was turned several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 43 publications
(66 reference statements)
7
47
0
Order By: Relevance
“…The VS content shows no consistent trend, as also observed by Poulsen and Bester (2010) for the same type of compost, indicating that the compost is not easily degradable. This is likely due to evaporation from the compost piles over time, as no irrigation took place.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The VS content shows no consistent trend, as also observed by Poulsen and Bester (2010) for the same type of compost, indicating that the compost is not easily degradable. This is likely due to evaporation from the compost piles over time, as no irrigation took place.…”
Section: Resultssupporting
confidence: 54%
“…Representative sampling for characterizing compost properties and process conditions is therefore difficult, especially owing to the small sample sizes often required for measurements (Poulsen and Bester, 2010). To improve sample homogeneity and representativity, Poulsen and Bester (2010) suggested collecting a set of primary samples (e.g. The sample should further be collected and handled so as not to affect properties that are to be measured.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the moisture content should be reduced to an appropriate level for the subsequent disposal, and this should become a principal part of SS treatment (Huang et al, 2014). SS management in which dewatering plays a significant part accounts for between 49 and 53% of the total operating costs (Murray et al, 2008;Hospido et al, 2010), and improper treatment may lead to repollution because of the large amounts of pollutants in SS (VerBerkmoes et al, 2009;Poulsen and Bester, 2010). Consequently, drying SS poses economic and environmental challenges for WWTPs and municipalities around the globe (Raynaud et al, 2012;Jin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of OP in almost every environmental matrix, including surface and ground water, air, soil, sewage and sludge, demonstrates the extent and persistence of these pollutants [1,2,3,4,5,6,7]. It has also recently been demonstrated that urinary metabolites of OP can be seen in the general human population at background levels [8].…”
Section: Introductionmentioning
confidence: 99%